2017
DOI: 10.1097/ccm.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Inferior Vena Cava Collapsibility to Predict Fluid Responsiveness in Spontaneously Breathing Patients With Sepsis and Acute Circulatory Failure

Abstract: The collapsibility index of the inferior vena cava during a deep standardized inspiration is a simple, noninvasive bedside predictor of fluid responsiveness in nonintubated patients with sepsis-related acute circulatory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 34 publications
4
101
0
4
Order By: Relevance
“…In women who had ΔVTI (supine‐legs elevated) values between 8% and 21%, the measurement was inconclusive for the prediction of hypotension; however, we could predict hypotension or its absence with a high sensitivity or specificity in 70% of cases. This performance is higher than that of other measurements used in clinical practice, emphasising the potential importance of ultrasound in obstetrics .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In women who had ΔVTI (supine‐legs elevated) values between 8% and 21%, the measurement was inconclusive for the prediction of hypotension; however, we could predict hypotension or its absence with a high sensitivity or specificity in 70% of cases. This performance is higher than that of other measurements used in clinical practice, emphasising the potential importance of ultrasound in obstetrics .…”
Section: Discussionmentioning
confidence: 73%
“…Several ultrasound measurements have been proposed as tools for predicting fluid responsiveness. These include inferior vena cava collapsibility, aortic blood flow peak velocity and even carotid flow . However, none of these has been validated in the pregnant population.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies in spontaneously ventilating adults have reported the accuracy of respiratory variation in IVC diameter as a predictor of fluid responsiveness, [34][35][36][37][38][39][40] with a pooled AUROC of 0.76. 24 The majority of these studies enrolled mixed patient populations, including those with trauma, dehydration and postoperative surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound evaluation of the inferior vena cava (IVC) can provide valuable information. If the IVC is dilated (>2.5 cm) and fails to collapse during the respiratory cycle, it is unlikely that the patient will respond to additional fluid; whereas a decline of >25%‐40% in diameter during respiration is highly predictive of fluid responsiveness …”
Section: Recognition and Treatment Of Volume Overloadmentioning
confidence: 99%
“…If the IVC is dilated (>2.5 cm) and fails to collapse during the respiratory cycle, it is unlikely that the patient will respond to additional fluid; whereas a decline of >25%-40% in diameter during respiration is highly predictive of fluid responsiveness. 35,36 Improvements in ultrasound technology have led to the use of bedside lung ultrasonography as a way to assess fluid overload. The finding on lung ultrasound of "B-line" artifacts (comet tail like vertical projections from the pleura) indicates fluid within the intra-alveolar septum.…”
Section: In the Australian And New Zealandmentioning
confidence: 99%